Automatic Watering of Potted Plants Using Arduino-Based Real-Time Clock - Ihsan, Hayatul; Zulfikar, Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
In the era of rapid technological development, humans rely on tools and technology to make their work easier, making technology a basic need. This study aims to design a device for watering plants automatically with time settings. This tool uses RTC DS 3231 which functions to set the watering time that has been determined by the user and sends commands to the Arduino nano to turn on the bc547 transistor so that the pump can water according to the schedule that is set automatically. The research methodology is carried out by designing, creating, and implementing system components including Arduino nano as a controller, and bc547 transistor to turn the water pump on and off. The study's results prove that the tool made can function properly and be developed as expected by the researcher. This tool works automatically based on the watering time determined according to the user's wishes.